In Vitro Rooting of Poplar: Effects and Metabolism of Dichlorprop Auxin Ester Prodrugs - Hajer Darouez; Stefaan P. O. Werbrouck (Plants)
Efficient adventitious root formation is essential in micropropagation. Auxin prodrugs, inactive precursors that convert into active auxins within the plant, offer potentially improved rooting control and reduced phytotoxicity. This study investigated the efficacy of dichlorprop ester (DCPE), commercialized as Corasil® and Clemensgros® (originally intended to increase grapefruit size), in promoting in vitro root initiation in the model plant Populus × canadensis, compared to its hydrolyzed form DCP and the related compound C77. DCPE displayed a stronger root-inducing effect than DCP, especially at lower concentrations (0.01 and 0.1 µM). Notably, at 1 µM, both DCP and DCPE induced abundant aerial root formation, a phenomenon not previously observed in poplar with traditional auxin treatments. Metabolite analysis revealed distinct patterns. DCPE treatment resulted in rapid hydrolysis to DCP, leading to faster and more systemic distribution of the active auxin throughout the plant, compared to direct DCP application. C77 treatments showed slower uptake and limited translocation combined with slow metabolism to DCP. These results highlight the potential of auxin prodrugs like DCPE as an effective and controllable auxin source for optimizing in vitro rooting protocols in woody plant species.